Literasi Digital "Cerdas–Kritis–Aman" bagi Warga Desa Cisitu, Kabupaten Sumedang - Furqon, Muhamad; Yusman, Nova Indrayana (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
This community service aims to improve the digital literacy skills of residents in Cisitu Village, Sumedang Regency through a socialization program themed "Smart–Critical–Safe". The background of this activity is the low level of digital literacy in rural communities, which impacts their vulnerability to hoaxes, disinformation, and cyber security threats. The service partners are residents of Cisitu Village consisting of various age groups and educational backgrounds. The method used is Participatory Action Research (PAR) with an interactive socialization approach, demonstration of safe digital technology use, and group discussions. The results showed a significant increase in participants' understanding of how to identify hoax information, digital security practices, and responsible social media use. Activity evaluation was conducted through pre-test and post-test showing an average increase in participant knowledge of 65%. This activity provides an important contribution in building a smart, critical, and safe digital society in the digitalization era.